Continuing education and employment creation: Investment in entrepreneurship matters. Issue 3 (27th May 2021) - Biney, Isaac Kofi
ABSTRACT: This paper explores continuing education and employment generation in Ghana. It places emphasis on entrepreneurship, and how continuing education could help students' create jobs. It used Bachelor of Administration final year students at Accra Learning Center as a unit of analysis. It is a qualitative study which sought to understand, determine the range of responses, and secure deeper insights and meaning into what it takes to become a successful entrepreneur. In-depth interview guides were conducted with 14 purposively selected students. It came to light that, in addition to classroom learning, students' participation in short seminars and workshops equipped them to become creative thinkers, take informed risks, create jobs, and envision a better future for themselves. It concludes that students' lifetime experiences should be allowed to supplement the classroom lecture.